Effect of Tube Voltage (kV) on Radiographic Image Quality of TOR-CDR Phantom Object - Fauzya, Sholy Putri (Universitas Negeri Semarang, 2022)
The test object was selected in the form of a TOR-CDR phantom which was exposed to X-rays with a low tube voltage (kV) and adjusted the contrast enhancement in the radiographic image. The study of this method was carried out by varying the tube voltage (kV) from 60 kV-80 kV and increasing contrast from 5%-30%. Based on the tests carried out, increasing the tube voltage (kV) can improve image quality, but increase the radiation dose received. However, giving enhancement can reduce tube voltage (kV) and improve image quality. The decrease in the average pixel value against the contrast on the TOR-CDR phantom follows the second order of polynomial equations, y=Ax2+Bx+. The coefficient A, B and C has linear relationship with the tube voltage (kV). The coefficient A has a decreasing trend and the coefficient B has an increasing tendency as the tube voltage (kV) increase. Meanwhile, the coefficient C shows the noise level in the image. Contrast enhancement can reduce the tube voltage (kV) used, but this contrast increase can only be done in a limited way. In this research, the maximum contrast enhancement limit in the image is 10% with 12-13 visible circles from 17 circles on the object.